From Hive to Hope: Honeybee and Apiculture Derived Products in Pakistan - Munir, Mahroo; Hayat, Sikandar; Javaid, Zeshan; Irshad, Muhammad Atif (Biological and Clinical Sciences Research Journal, 2025)
Honeybees are vital for pollination, biodiversity, and the production of apicultural products. Their populations, however, are increasingly threatened by various environmental and biological stressors in Pakistan. Strengthening knowledge on their ecological and economic roles is crucial for sustainable conservation. Objective: To synthesize current evidence on honeybee species, apiculture development, economic potential of bee products, and the major threats to honeybee populations in Pakistan. Methods: This narrative review examined published literature, government reports, and apiculture data relevant to Pakistan. Sources were identified from major scientific databases and national records, with no time restrictions. Information on honeybee species distribution, apiculture production, export trends, and threats was extracted and descriptively analyzed to provide an updated overview for researchers and policymakers. Results: Pakistan hosts four honeybee species, with Apis mellifera being the predominant domesticated species. Despite growth in the apiculture sector, average honey yield remains below 12 kg per beekeeper, nearly half of the global average. Honey, pollen, propolis, beeswax, and royal jelly are produced, although honey remains the major export at approximately five million kilograms annually. Diverse biotic and abiotic pressures are causing significant declines in both wild and managed populations, while national data remain insufficient for informed conservation planning. Conclusion: Honeybees in Pakistan hold considerable ecological and economic value, yet their populations face multiple challenges that are inadequately documented. Strengthening research capacity, improving apicultural practices, and establishing targeted conservation strategies are essential to protecting honeybee diversity and ensuring sustainable resource use.